2023
DOI: 10.12669/pjms.39.5.7280
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy of EUS versus MRCP with ERCP as gold standard in patients presenting with partial biliary obstruction – finding a better diagnostic tool

Abstract: Objective: To evaluate the diagnostic accuracy of different imaging modalities in patients with partial biliary obstruction with no obvious aetiology on initial imaging. Methods: This is a prospective single-centre cohort study carried out at Pak Emirates Military Hospital, Rawalpindi from June 2019 to June 2021 with non-probability consecutive sampling. Patients with ages 16 to 75 years, presenting with partial biliary obstruction and undetermined aetiology on initial imaging (TUS and MRCP) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These results indicate a high number of false negatives for TUS in this study. Similar findings were reported by Khan and colleagues, who also found a low sensitivity of 29.2% [ 13 ]. Additionally, Makmun et al observed a low sensitivity range of 15-40% for detecting bile duct stones (choledocholithiasis) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results indicate a high number of false negatives for TUS in this study. Similar findings were reported by Khan and colleagues, who also found a low sensitivity of 29.2% [ 13 ]. Additionally, Makmun et al observed a low sensitivity range of 15-40% for detecting bile duct stones (choledocholithiasis) [ 14 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding aligns with the study conducted by Bansal and colleagues, where they concluded that the mean age of patients was 47.9 ± 18.87 years, with 54.7% female sufferers in the majority, compared to 45.3% male, contradicting the outcomes of multiple studies [ 9 ]. In contrast, Anwer et al [ 10 ], Wang et al [ 11 ], Netinatsunton et al [ 12 ], and Khan et al [ 13 ] found that 51.2%, 58.4%, 41.1%, and 58.5% of males were more affected and showed a high tendency to develop CBD stones than females, with mean ages of 50, 59, 55, and 50 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation